The Discursive Contestation of Care: A Critical Analysis of Medical Communication, Power, and Ethics in Heart of a Child (1994) - Budiarto Budiarto; Suhendar Suhendar (STIBA IEC JAKARTA, 2026)
This study provides a multi-theoretical discourse analysis of the 1994 film Heart of a Child, focusing on how language mediates institutional power, emotional vulnerability, and ethical decision-making in medical contexts. Drawing on Norman Fairclough's Critical Discourse Analysis (CDA), Mikhail Bakhtin’s theory of heteroglossia, Deborah Tannen’s distinction between “report-talk” and “rapport-talk,” John Gottman’s research on relational communication, and J.L. Austin and John Searle’s Speech Act Theory, this analysis demonstrates how clinical discourse functions as a centralizing force while parents’ emotional language provides a decentralized counter-discourse. The findings reveal that medical authority is actively performed and contested through linguistic choices, not merely asserted. The study emphasizes the historical tension between medical paternalism and the emerging emphasis on patient autonomy, particularly in relation to anencephalic organ donation. This paper contributes to the understanding of contemporary healthcare communication and bioethics by emphasizing the performative nature of medical decision-making